The Challenges Of Indonesia As A "Quintessential Transit Country" For Refugees: Cases Of Refugees In City Of Pekanbaru - Cifebrima Suyastri, Rika Isnarti, Rendi Prayuda (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
Indonesia is one of the Refugee Transit Countries and one of the largest in Asia. This situation also implies that Indonesia has other responsibilities to protect both its citizens and refugees. However, due to its position as a transit country, Indonesia, unlike final destination countries, does not have an obligation to protect refugees entirely. The purpose of this research is to analyze Indonesia's acceptance of refugees and the challenges it faces. The acceptance of refugees as a transit country and not a final destination for refugees will threaten Indonesia's economic, social, security and other sectors. The number of refugees in Indonesia and their continued detention is still increasing. This study utilizes the norm life cycle theory to determine the Indonesian reasons for accepting refugees. It collects information from focus group discussions or an in-depth interview with some of the NGOs in Pekanbaru, and library research, using qualitative method. Indonesia was found to be in the norm emergence stage and going to the norm cascade, although not entirely in the norm cascade phase. Within this theory, altruism and empathy are the dominant motives for the Indonesian reason to accept the refugees. In the case of the city of Pekanbaru, the challenges faced by Indonesia in dealing with refugees are a lack of service to refugees, particularly in terms of empowerment for the refugees, a high number of refugees imbalanced with detention facilities, and a lack of refugee handling due to the limitation of government policy.